Determinants of household resilience to food insecurity: A case of rural northern Ethiopia by using the RIMA approach - Habtamu Mossie; Tadsual Asfaw; Abebaw Abebe; Maria Fekete-Farkas (Journal of Agriculture and Food Research)
An ongoing and global agenda is the food security policy debate in rural Ethiopia of households to enhance resilience at the individual and household level for tackling food insecurity. Therefore, this study investigated determinants of household resilience to food insecurity in rural dwellers of Mekiet District. A cross-sectional research design was conducted in two agro ecological zones of the Mekiet district, lowland, and midland, involving 228 respondents. The study employed a quantitative and qualitative approach, with multi-stage sampling techniques results employed to select sample households by using two-stage factor analysis. The result from factor analysis using the RIMA approach showed that the latent variables of adaptive capacity, asset, and social safety net have a positive value of (0.76), (0.51), and (0.77), respectively, and in the contrast, access to essential services has a negative load of (-0.61), and all variables were found to be statistically significant. All those loads were significant, with an absolute value of factor loadings greater than 0.364, which is recommended for a sample size of 200 and above. Those variables were also highly correlated with resilience capacity. The study recommended that resilience programs should be implemented at district, community, and household levels to enhance resilience to food insecurity.